GENERAL DIRECTIONS OF DEVELOPMENT OF INNOVATIVE PROCESSES IN EDUCATION - Ortiqova Nargiza Akramovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the general areas of development of innovative processes in the field of Education.